Determinants of Bank's profitability: an empirical study from China commercial banks - SONG, YIPING (2012)
This article investigates determinants of China commercial banks’ profitability for the period 2004-2011, which is measured by return on average assets. This article uses several materials of domestic and foreign researches for reference. Firstly, I analyze profit statuses of China’s listed commercial banks. Then I classify factors of profitability into the bank’s specific factors, industry factors and macroeconomic factors so as to specifically analyze them combined with knowledge of economics, management and statistics. Eventually, I select the data of 6 sample banks during the period from 2004 to 2011 to make correlation analysis, variance analysis and regression testing on these factors and return on assets. The result indicates that bank’s own factors are the most influential one in the short term. Industry factors and external macroeconomic factors have a certain influence, which is much less than the bank’s own factors.